2011
DOI: 10.1002/bin.332
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of an Observation System for Recording Physical Activity in Children

Abstract: Although mechanical means of measuring physical activity are available, they cannot provide information about the context in which such activity occurs. Therefore, direct-observation systems remain essential tools for studying physical activity. The Observational System for Recording Physical Activity in Children (OSRAC) is a direct-observation system for recording physical activity and associated environmental variables. We evaluated the concurrent validity of the OSRAC physical activity codes with two types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 31 publications
4
23
1
Order By: Relevance
“…We used the activity codes specified in the Observational System for Recording Physical Activity, Preschool Version (OSRAC‐P; Brown et al, ; see also Larson, Normand, & Hustyi, ) to classify participant physical activity. Larson et al () reported data from four children (ages 3 to 5 years) who were instructed to engage for 1 min in a representative activity at each of the five OSRAC activity levels. The activity‐code measures covaried with both heart‐rate measures and pedometer step counts, suggesting that the codes are valid measures of physical activity for this age group.…”
Section: General Methodsmentioning
confidence: 99%
“…We used the activity codes specified in the Observational System for Recording Physical Activity, Preschool Version (OSRAC‐P; Brown et al, ; see also Larson, Normand, & Hustyi, ) to classify participant physical activity. Larson et al () reported data from four children (ages 3 to 5 years) who were instructed to engage for 1 min in a representative activity at each of the five OSRAC activity levels. The activity‐code measures covaried with both heart‐rate measures and pedometer step counts, suggesting that the codes are valid measures of physical activity for this age group.…”
Section: General Methodsmentioning
confidence: 99%
“…Because research suggests that the activity codes specified by the Observational System for Recording Physical Activity in Children (OSRAC; McIver, Brown, Pfeiffer, Dowda, & Pate, ) are valid measures of physical activity in young children (Larson, Normand, & Hustyi, ), we used these codes to score the activity level of participants during the baseline observations and all experimental conditions (see Table ). However, the discontinuous measurement strategy (i.e., 5 s of observation followed by 25 s of recording) reported by McIver et al () was not used.…”
Section: Methodsmentioning
confidence: 99%
“…In the studies noted above, physical activity was measured using either strictly observational measures (i.e., the OSRAC) or mechanical measures (i.e., pedometers, accelerometers). In some cases, children may produce similar step counts, but idiosyncratic HRs (Larson et al ; Van Camp & Berth, ). Steps as a primary measure of PA may also be problematic when children engage in behaviors that do not involve translocation (Van Camp & Berth, ).…”
mentioning
confidence: 99%